The Level of Integration of Select International Markets in COVID Crisis: An Empirical Assessment - Sarkar, Joy; Paul, Raju (Indian Journal of Research in Capital Markets, 2024)
Purpose : Due to a lack of data, only seven countries were taken into consideration when analyzing the relationship between FPI inflow and market integration. This paper began with stock market indices of 20 developed and developing countries in order to assess the factors that influence, positively or negatively, international investors to choose the Indian market for their funds despite the growth crisis generated by the great COVID pandemic. The study period was selected from January 1, 2019, to July 31, 2023, which was further subdivided into three sub-periods: Pre-COVID, COVID, and Post-COVID periods. Methodology : In order to determine whether the unexpected emergence of the pandemic caused any changes in the log return series of the selected market indices, a correlation test—one of the straightforward, useful methods of assessing the association or integration of markets—was performed on the data. The benefits of foreign diversification were properly illustrated by a tabular display of the monthly average FPI assets under custodian (AUC) and level of integration. Findings : International investors are encouraged to choose India as a good destination for their fund investments due to the declining trend of correlation between the Indian market and other select markets over the sub-periods found in this paper. This suggests low integration, which may reduce or even eliminate idiosyncratic risk. Practical Implications : This study would help investors, analysts, portfolio managers, fund managers, policymakers, and others to gauge the flow of capital in the Indian capital market. Originality : This study, in contrast to other research, compared the market results of seven countries with a monthly average of the FPI AUC investment in India by country in order to ascertain whether capital influx into India during COVID-19.